Orchestrating Good Educational Relationships With(in) Automated Teaching: A Posthuman Perspective - Gibson, Patricia (Proceedings of the International Conference on Networked Learning, 2024)
Automated teaching tends to be underpinned by learning approaches that are personalised and adaptive by nature. This individualistic vision of education shapes our conception of knowledge and how it is created. Here, knowledge becomes objectified in the form of a quantifiable commodity in a commercial market. Consequently, knowledge creation becomes conceptualised as the transmission of this object from automated teacher to student. The human teacher is positioned outside the educational process, often to the point of exclusion. This research moves beyond a vision of automated teaching that is framed by learning approaches, where teaching approaches remain starkly absent. I coded an automated teacher in the form of a Teacherbot — a chatbot that functions as a teacher — to work with a group of Interactive Media students at a UK University. Posthuman critical theory is used to conceptualise knowledge and its creation as a process of relational encounters, rather than a transmissive object. The findings chart the transformations in student understandings around what constitutes knowledge and its creation. The emergent pedagogical encounters that brought about these student transformations are identified through the nature of the teaching relationships: the performance of an obligation of radical hope; the creation of disturbances; and, trust and the pursuit of risk. This paper is significant in its call to bring teaching back to automated teaching systems.